Organização do trabalho e controle em teleatendimento: o caso de uma empresa de cobrança - Ricci, Marlucy Godoy (2010)
The purpose of this study was to explore the peculiarities of the work organization and the different ways of control that were observed in the call center operator s activity. The theoretical-methodological focus that led the research is the Work Organization. A bibliographic research and a case study were performed. The bibliographic research allowed the characterization of the area, its emergence and development, as well as many aspects of the work in this activity. The field research was performed at a company that does collection service over the telephone and involved some visits to the company plant and the incorporation of interviews with the operators, support staff, main executives and operation manager. The interviews allowed the interviewees to explain how they operate, how they evaluate their job, how they deal with different demands and also their perspective regarding the future of this activity. The literature shows that the employees who have contact with the clients, as telemarketing operators, experience a double control, practiced on one hand by the company norms and rules and on the other hand by each client s specific demands. In the studied company it was noticed that the operators, besides the company and the clients, have to deal with other souces of embarassment.